New prodrugs of Adefovir and Cidofovir - Tichý, Tomáš; Andrei, Graciela; Dračínský, Martin; Holý, Antonín; Balzarini, Jan; Snoeck, Robert; Krečmerová, Marcela (Bioorganic & medicinal chemistry, 2011)
New Adefovir (PMEA) prodrugs with a pro-moiety consisting of decyl or decyloxyethyl chain bearing hydroxyl function(s), hexaethyleneglycol or a (5-methyl-2-oxo-1,3-dioxolen-4-yl)methyl unit were prepared starting from the tetrabutylammonium salt of the phosphonate drug and an appropriate alkyl bromide or tosylate. Analogously, two esters of Cidofovir [(S)-HPMPC] bearing a hexaethyleneglycol moiety were prepared. The activity of the prodrugs was evaluated in vitro against different virus families. A loss in the antiviral activities of the hydroxylated decyl or decyloxyethyl esters and hexaethyleneglycol esters of PMEA against human immunodeficiency virus (HIV) and herpesviruses [including herpes simplex virus (HSV), varicella-zoster virus (VZV), and human cytomegalovirus (CMV)] occurred in comparison with the parent compound. On the other hand, the (5-methyl-2-oxo-1,3-dioxolen-4-yl)methyl ester of PMEA showed significant activities against HIV and herpesviruses. (S)-HPMPC prodrugs exhibited anti-cytomegalovirus activities in the same range as the parent drug, whereas the anti-HSV and anti-VZV activities were one- to seven-fold lower than that of Cidofovir.
Keywords: Adenine; nádorové buněčné linie; cytosin; Cytomegalovirus; Herpesvirus 3, Human; Cidofovir; adenin; antivirové látky; Cell Line, Tumor; Organophosphonates; Prodrugs; virus varicella zoster; zvířata; Humans; cidofovir; prekurzory léčiv; HIV; Cytosine; Antiviral Agents; organofosfonáty; Simplexvirus; lidé; Animals